Reduzierung des Neorefluxes an der V. saphena magna Crosse durch extensive Crossektomie - Frings, N.; Frings, A.-C.; Tran, P.; Schubert, R. (Phlebologie, 2010)
Background: Neovascularisation (NV) at the saphenofemoral junction (SFJ) is an important cause of recurrent great saphenous varicose veins. Unfortunately up to now no surgical technique at the SFJ could prevent neoreflux completely. We present a new technique at the SFJ with the aim to reduce the rate of neoreflux.Material and Methods: In a prospective study 100 patients (100 SFJ ligations) with extensive crossectomy were included. Extensive crossectomy means: Flush ligation of the SFJ, oversewing the endothelium stump with Prolene®(4 x 0), ligation of the side branches as far away as possible from the SFJ and electrocoagulation of the free endothelium of these side branches. Mean age 47 years (18–65), female/ male 69 %/31 %, ASA-classification I–II (100 %), CEAP-classification C2 59, C3 25, C4 16. All patients could be examined by colour duplex scan after two/three days, three months and one year and 68 patients after two years.Results: Duplex imagines identified neoreflux at the SFJ in two patients (2 %) after one year and in only one patient (1.5 %/ 68 patients) after two years. This female patient was pregnant (31st week) and had recurrent varicose veins with origin mostly from an insufficient Dodd perforator vein. The other patient with reflux at the first examination showed no more reflux after two years.Conclusion: Recurrent reflux in the groin by neovascularisation was strongly reduced by our technique of extensive crossectomy. Up to know no other technique to prevent NV (patch, barrier technique) has shown such favourable results. The technique is easily performed and has no further complication than a simple ligation of the SFJ.
Keywords: Varicose vein surgery; recurrence; neovascularisation